Association Between Elevated Pulse Pressure and High Resting Coronary Blood Flow Velocity in Patients With Angiographically Normal Epicardial Coronary Arteries - Maria Lembo; Rosa Sicari; Roberta Esposito; Fausto Rigo; Lauro Cortigiani; Francesco Lo Iudice; Eugenio Picano; Bruno Trimarco; Maurizio Galderisi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundThe aim of our study was to evaluate the relationship of pulse pressure (PP), a raw index of arterial stiffness, with noninvasively determined coronary flow reserve (CFR) and its components, in patients with angiographically normal epicardial coronary arteries. Methods and ResultsThe study population included 398 patients without angiographic evidence of coronary stenosis, who underwent high‐dose dipyridamole stress echocardiography with transthoracic‐derived CFR evaluation on the left anterior descending artery. CFR was calculated as the ratio between high‐dose dipyridamole and resting coronary diastolic peak velocities. Patients were divided into 2 groups: the first group included the first and second PP tertiles (n=298, PP ≤60 mm Hg) and the second group included the highest PP tertile (n=100, PP >60 mm Hg). Mean blood pressure, systolic blood pressure (both P<0.0001), age (P<0.002), and left ventricular mass index (P=0.013) were higher in the highest PP tertile, which also showed higher resting coronary flow velocity (31.6±9.6 cm/s versus 27.7±6.4 cm/s, P<0.0001) and marginally lower CFR (2.5±0.6 versus 2.6±0.6, P=0.044). Hyperemic coronary flow velocity did not differ between the 2 groups. By separate multiple linear regression analyses, after adjusting for sex, age, the highest systolic blood pressure tertile (≥140 mm Hg), left ventricular mass index, and cardiovascular risk factors, the highest PP tertile was associated with resting coronary flow velocity (P=0.003) and only marginally with hyperemic coronary flow velocity (P<0.02), whereas its association with CFR was not significant. ConclusionsIn patients without epicardial coronary artery stenosis, the highest PP tertile is associated with an increased coronary flow velocity at rest.